1994
DOI: 10.1002/bjs.1800810536
|View full text |Cite
|
Sign up to set email alerts
|

Life-table analysis of stomal complications following ileostomy

Abstract: Stomal complications of ileostomy may occur many years after construction. An actuarial analysis of complications of 150 permanent end ileostomies constructed over a 10-year period is reported. By 20 years the incidence of stomal complications approached 76 per cent in patients operated on for ulcerative colitis and 59 per cent in those with Crohn's disease (P < 0.05). Revisional surgery rates were higher in patients with ulcerative colitis than in those with Crohn's disease (28 versus 16 per cent), albeit not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
0
9

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 12 publications
6
138
0
9
Order By: Relevance
“…Data derived from numerous studies showed that the most common stomal complication was para-stomal skin excoriation ranging from 5.9 to 43.8% in a loop ileostomy and 8 to 34% in an end ileostomy (Table 5) [10,[16][17][18][19][20][21][22]. In the present study, the incidence of skin excoriation was much 3 In an end ileostomy however, the opening made in the stoma appliance is smaller and better fitting because it has to cover only a single barrel of small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Data derived from numerous studies showed that the most common stomal complication was para-stomal skin excoriation ranging from 5.9 to 43.8% in a loop ileostomy and 8 to 34% in an end ileostomy (Table 5) [10,[16][17][18][19][20][21][22]. In the present study, the incidence of skin excoriation was much 3 In an end ileostomy however, the opening made in the stoma appliance is smaller and better fitting because it has to cover only a single barrel of small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Skin excoriation from leakage remains the most common complication of an ileostomy, particularly in badly sited stoma, where application of an appliance is improper [1][2][3]. Intestinal contents through a proximal ileostomy, cause extreme excoriation of the skin, making further application of the appliance difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Često se događa da prilikom čišćenja stome ili zamjene vrećice sluznica stome blago krvari (što je klinički beznačajno), ali ako se ustanovi jače krvarenje, potrebno je zatražiti liječničku pomoć 5 . Stoma je vizualno najčešće okruglog oblika, no ponekad može biti i ovalna.…”
Section: Komplikacijeunclassified